2010
DOI: 10.1186/1471-2350-11-132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating gene by sex and age interactions on cardiovascular risk factors in Brazilian families

Abstract: BackgroundIn family studies, it is important to evaluate the impact of genes and environmental factors on traits of interest. In particular, the relative influences of both genes and the environment may vary in different strata of the population of interest, such as young and old individuals, or males and females.MethodsIn this paper, extensions of the variance components model are used to evaluate heterogeneity in the genetic and environmental variance components due to the effects of sex and age (the cutoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Regarding the fixed effects (covariates) used in the model, we opted for sex, age, age 2 , and interactions between those, which comprise the model most recommended in genetic studies [15,16,23]. In order to account for the ancestry background in our sample, we also included and tested ancestry coefficients that are the two main principal components (pca1 and pca2) estimated for our sample from the Brazilian population as previously described [24].…”
Section: Models and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the fixed effects (covariates) used in the model, we opted for sex, age, age 2 , and interactions between those, which comprise the model most recommended in genetic studies [15,16,23]. In order to account for the ancestry background in our sample, we also included and tested ancestry coefficients that are the two main principal components (pca1 and pca2) estimated for our sample from the Brazilian population as previously described [24].…”
Section: Models and Statistical Analysismentioning
confidence: 99%
“…The heritability estimates for PA traits were calculated through the variance components approach implemented in SOLAR-Eclipse 8.3.1 package. Assuming the trait follows a normal distribution, the covariance between traits for individuals i and i′ is given by [15]:…”
Section: Models and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies identified that age-at-onset is a useful trait for gene mapping of common complex diseases 21 and reported that heterogeneity in trait variances needs to be accounted for in the design and analyses of trait orientated gene finding studies. 22 Lifestyle factors, including physical activity 23 and smoking 24 have also been a focus of the study. The study has been extended to also include aspects of mental health, another major non-communicable disease complex forming a large burden to society.…”
Section: Findings To Datementioning
confidence: 99%
“…The Baependi Heart Study is the first studies in Brazil clustering families for analyze the relationship between genetic and cardiovascular risk factors [1][2][3][4][5][6]. It had started in 2005 with partnerships among some Brazilian Universities for research and outreach projects.…”
Section: Introductionmentioning
confidence: 99%